Low-carbon economic dispatch of integrated energy system based on liquid carbon dioxide energy storage - Zhang, Jie; Chen, Jie; Ji, Xiaoning; Sun, Hanzhe; Liu, Jing (Frontiers in Energy Research, 2023)
Aiming at the problem of how to realize the system low-carbon economic dispatch and renewable energy consumption, liquid carbon dioxide energy storage (LCES) and carbon capture system (CCS) are introduced into the integrated energy system economic dispatch model. This paper proposed a low-carbon economic dispatch model for the integrated energy system that took into account LCES and CCS, and considered the carbon trading mechanism, aiming to minimize the total operating cost of the system. Analy and contrasted the situation of LCES and battery energy storage in the operation of integrated energy system. This comprehensive energy system was simulated by CPLEX simulation software, and the dispatching results were analyzed from different perspectives such as electric energy, thermal energy, and CO2 emissions. These results show that the proposed model effectively reduces carbon emissions, improves energy utilization, and achieves comprehensive Low-carbon economic operation of the energy system.